2009
DOI: 10.3832/ifor0475-002
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the carbon budget of intensive forest monitoring sites in Germany using the simulation model BIOME-BGC

Abstract: It is shown that by calibrating the simulation model BIOME-BGC with mandatory and optional Level II data, within the ICP Forest programme, a well-founded calculation of the carbon budget of forest stands is achievable and, based on succeeded calibration, the modified BIOME-BGC model is a useful tool to assess the effect of climate change on forest ecosystems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…This offers many options for integrated evaluations of soil data with other temporal assessments on the same plots such as crown condition, foliar chemistry, or tree growth, allowing in-depth analyses with mechanistic models (e.g. van der Salm et al 2007;Reinds et al 2008;Jochheim et al 2009;Mol Dijkstra et al 2009) in order to better understand cause-effect relationships in forest processes and responses to environmental impacts (Lorenz and Fischer 2013).…”
Section: Potentiality Of Databasementioning
confidence: 99%
“…This offers many options for integrated evaluations of soil data with other temporal assessments on the same plots such as crown condition, foliar chemistry, or tree growth, allowing in-depth analyses with mechanistic models (e.g. van der Salm et al 2007;Reinds et al 2008;Jochheim et al 2009;Mol Dijkstra et al 2009) in order to better understand cause-effect relationships in forest processes and responses to environmental impacts (Lorenz and Fischer 2013).…”
Section: Potentiality Of Databasementioning
confidence: 99%
“…Jochheim et al (2009) simulated NPP values between 5 and 7 t C ha -1 year -1 for Scots pine, beech and Norway spruce forests on nine level II plots in Germany. Similarly to our results, they found that the differences in NPP between sites are larger than between the different tree species.…”
Section: Model Evaluationmentioning
confidence: 99%
“…The model has been widely applied across a range of forested ecosystems around the world, has been extensively compared with flux measurements (Schimel et al 2000), and was specifically parameterized and validated for major central European species by Pietsch et al (2005). Norway spruce in particular has been widely studied with BIOME-BGC , Lange 2007, Jochheim et al 2009), giving confidence that the model can accurately represent spruce growth across a range of different circumstances. Forest management operations were included in BIOME-BGC by and , based on prescribed management regimes.…”
Section: Methodsmentioning
confidence: 99%